Resistance to malaria through structural variation of red blood cell invasion receptors - Leffler, E; Band, G; Clarke, G; Kivinen, K; Le, Q; Clarke, G; Bojang, K; Conway, D; Jallow, M; Sisay-Joof, F; Bougouma, E; Mangano, V; et al. (American Association for the Advancement of Science, 2017)
Plasmodium falciparum invades erythrocytes via interactions with proteins on the host cell surface. By analyzing genome sequence data from human populations, including 1269 African individuals, we identify a diverse array of large copy number variants affecting the erythrocyte invasion receptor genes GYPA and GYPB. We find that a nearby association with severe malaria is explained by a complex structural rearrangement that involves the loss of GYPB and gain of two hybrid genes, each with a GYPB extracellular domain and GYPA intracellular domain. This variant reduces the risk of severe malaria by 40% and has recently risen in frequency in parts of Kenya. We show that the structural variant encodes the Dantu blood group antigen, a serologically distinct red cell phenotype. Thus structural variation of erythrocyte invasion receptors is associated with natural resistance to severe malaria.